Efficiency effects of cross-border medical demand - Daniel Lukas (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
There is a growing interest in cross-border medical care and its comparative advantages. In addition, medical care can be defined as a local assurance good. Little research is being carried out in this field. This paper discusses the individual considerations for medical treatment offered at home and abroad within a micro-economical framework. Specific assumptions as mistrust, monetary and non-monetary transaction-costs, a price and cost gradient, illness severity as well as a lump-sum insurance are discussed. We show that a demand abroad can be utility maximizing, however, only second best. There are inefficiencies in the dimensions of ex-post demand and income risk either on the side of gross-income or of costs. Furthermore, the foreign demand is restricted for low health stages driven by mistrust and restrictions in quality. Higher stages are more capable if fixed costs are low. To demand abroad the marginal treatment costs abroad must fall short of a threshold level. Finally, an out-of-pocket payment can reduce the moral hazard when treatment takes place abroad.
Keywords: I19; F1; D01; D80; R23; 330; cross-border medical care; health tourism; efficiency; patient migration; trust; Gesundheitswesen; Konsumentenverhalten; Internationaler Tourismus; Vertrauen; Wirtschaftliche Effizienz; Krankenversicherung; Moral Hazard; Theorie